Project implementation of strengthening “Profil Pelajar Pancasila” (P5) as a value of life in elementary schools - Kardiana Metha Rozhana; Sugiharto Firsta Bagus; Muhammad Fauzy Emqy; Antonius Alam Wicaksono (Jurnal Bidang Pendidikan Dasar, 2023)
This study discusses the independent curriculum which has begun to be implemented in elementary schools, but there are still several schools that have difficulty implementing P5 activities. The purpose of this study was to identify the Project for Strengthening “Profil Pelajar Pancasila” (P5) implemented in elementary schools for reading literacy in other schools. The research method used is descriptive qualitative with data collection techniques of observation, interviews, FGDs, and documentation. The object of this research was carried out at SDN Merjosari 4 Malang City in May. The results of this study are that through P5 activities students get provision for character education in accordance with the 6 P5 Dimensions, namely Faith, Fear of God Almighty, Global Diversity, Mutual Cooperation, Critical Reasoning, Independent, Creative.